Anterolateral Ligament Reconstruction: Surgical technique in anterior cruciate ligament reviews. Issue 1 (31st January 2017) - Zordan, J.; Etcheto, H. Rivarola; Blanchod, C. Collazo; Palanconi, M.; Salinas, E. Álvarez; Autorino, CM; Escobar, G.
Anterior cruciate ligament (ACL) reconstruction is a common procedure in daily practice with 75 to 97% excellent long-term results. But in certain cases, some patients perceive rotational instability, for this reason the revision rate can be 10 to 15%. Objectives: evaluate functional outcome in revisions of ACL reconstruction associated with ALL. Methods: Between July 2015 and February 2016 (11 knees) Eleven Revision ACL reconstruction were performed with ALL with double incision technique performed by the same surgical team. Inclusion criteria were: ACL reconstruction failures with a grade 2 or 3 Lachman test, a grade 3 pivot-shift without other ligamentary injury lesions associated and complete range of motion. Results: The concept of rotational instability associated with ACL injury has been described more than a decade ago. However, there is no consensus on how to quantify rotational instability in ACL injuries; so when associating an extracapsular technique. Currently there is a lack of high-level evidence comparing isolated ACL repair and associated with the modified reconstruction of ALL that allows us to define therapeutic approaches. The ALL reconstruction associate an ACL reconstruction remains a matter of study. Conclusion: We obtain excellent results in antero – posterior and rotational stability after performing the procedure.